Cetirizine modifies quality of life and symptoms in children with seasonal allergic rhinitis: a pilot study - Benazzo, Marco; Leonardi, Salvatore; Corsico, Angelo; Licari, Amelia; Miraglia del Giudice, Michele; Peroni, Diego; Salpietro, Carmelo; Marseglia, Gian Luigi; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2020)
Background and aim Seasonal allergic rhinitis (SAR) is a common disease in childhood that is characterized by bothersome symptoms and impaired quality of life (QoL). As histamine is the pivotal pathogenic mediator in SAR, antihistamines are the first-line option in the treatment. Cetirizine is a well-known effective antihistamine. This real-life pilot study aimed to investigate the effectiveness of a 4-week continuous cetirizine treatment in a group of Italian children with SAR. Methods Total symptom score (TSS) and the Pediatric Rhinoconjunctivitis Quality of Life Questionnaire (PRQLQ) were assessed at baseline and the end of the treatment. Results Cetirizine significantly improved QoL (in all domains) and symptom severity (p<0.001 for both). Conclusions The present preliminary study showed that a 4-week cetirizine treatment was able to improve QoL significantly. Cetirizine treatment also significantly reduced symptom severity in Italian children with SAR and was safe.